The morphology of polyvinylpyrrolidone nanofibers containing Anredera cordifolia leaves - Sriyanti, Ida; Almafie, Muhammad Rama; Nugraha, Yuda Prasetya; Idjan, Meutia Kamilatun Nuha Ap; Jauhari, Jaidan (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
The electrospinning method has been used successfully to make polyvinylpyrrolidone nanofiber containing Anredera cordifolia leaves (BLE). The research methods used were qualitative and pure experiment method. Polyvinilpirolidone nanofibers containing BLE were prepared with three mass variations of the polyvinylpyrrolidone (% w/w), namely 12%, 10%, and 8% w/w, respectively. The results of the macroscopic photo show that the fiber structure looks white for PVP nanofibers and yellow for PVP/BLE nanofibers. The fiber morphology was analyzed using SEM and the results showed that PVP and all PVP/BLE nanofibers were like a continuous strand of crossbars with a diameter of 590 – 1190 nm. The decrease in the concentration of the PVP polymer led to a reduction in the diameter of the resulting nanofibers. The coefficients of variance (ε), of the PVP, BLE1, BLE2, and BLE3 nanofibers were 0.06, 0.09, 0.11, and 1.22, respectively. The physicochemical structure of the nanofibers was evaluated using XRD and FTIR. The chemical analysis (FTIR) showed that there was a molecular interaction between Anredera cordifolia leaves extract and polyvinylpyrrolidone in the form of hydrogen bonds. The physics analysis (XRD) shows the effect of the electrospinning process, which is to change the structure of BLE crystals to semi crystals. The application of PVP/BLE nanofiber for wounds dressing